Multi-objective integrated production planning model and simulation constrained doubly by resources and materials - Wang Cheng; Liu, Xiao bing; Zhao, Guo zhi; Chin, Kim On (2016)
Based on analysing the defects of ERP planning system and researching related literatures, a multi objective integrated production planning model is constructed which is constrained double by resources and materials. The model tekes delivery on-tome, reduces inventory , reduces overtime work, meintains safety inventory as its optimization objectives, and can achieve the integrated optimization method provided by the model has strong feasibility and effectness.